Breach of Contract in Digital Transactions on the Itemku Platform: A Case Study of Consumer Rights Violations in Streaming Subscription Services - Tantaru, Fernando; Soplantina, Valentino Dinatra (Batulis Civil Law Review, 2025)
Introduction: This article examines the issue of breach of contract in digital transactions on the Itemku platform, focusing on consumer rights violations in streaming subscription services. The study investigates the inadequacies in existing consumer protection laws in Indonesia, particularly regarding digital commerce.Purposes of the Research: The purpose of this research is to analyze the legal responsibilities of digital platforms in preventing breaches by third-party sellers and to explore the available legal remedies for consumers facing violations of their rights in the digital marketplace.Methods of the Research: Employing a normative legal research method, this study utilizes a statutory and conceptual approach to assess the current legal framework and its implications for consumer protection.Results Main Findings of the Research: The findings reveal significant gaps in legal protections for consumers in digital transactions, particularly regarding the accountability of platforms like Itemku. The research indicates that without effective regulatory measures, consumers remain vulnerable to various forms of breach. Recommendations include enhancing internal policies for seller accountability and adapting legal frameworks to better address the complexities of digital commerce.